2013
DOI: 10.19026/rjaset.6.4096
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Color Pigments Removal from Palm Oil by Activated Ukpor Clay Using Response Surface Methodology

Abstract: The aim of this study was to investigate the optimum operating process parameters during the adsorption of color pigments from palm oil onto activated Ukpor clay using Response Surface Methodology (RSM). The clay was activated using sulphuric acid solution. The process parameters investigated include; temperature, time, adsorbent dosage, adsorbent/oil ratio and stirring speed. The results showed that the bleaching efficiency was significantly affected by the linear, quadratic and some of the interaction terms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…It is seen that the three elaborated models present a similarity between the coefficients signs of the different terms (linear, quadratic and multiple), which implies that the bleaching capacity of the bleaching clay at each maximum wavelength varies in the same way (increase or decrease). The examination of these models reveals that the positive values of the coefficient of temperature (X1), clay dosage (X2) and contact time (X3) indicate that an increase in these factors involves an increase in the bleaching capacity, similar results have been found by the following authors (Ajemba et al 2013;Nwabanne et al 2013). However, the clay dosage and the temperature respectively have a more significant effect on bleaching capacity since their coefficients are higher, while the negative values of the other coefficients mainly those of quadratic and multiple terms cause a decrease in the bleaching capacity.…”
Section: The Models Coefficients Sign Interpretationsupporting
confidence: 74%
“…It is seen that the three elaborated models present a similarity between the coefficients signs of the different terms (linear, quadratic and multiple), which implies that the bleaching capacity of the bleaching clay at each maximum wavelength varies in the same way (increase or decrease). The examination of these models reveals that the positive values of the coefficient of temperature (X1), clay dosage (X2) and contact time (X3) indicate that an increase in these factors involves an increase in the bleaching capacity, similar results have been found by the following authors (Ajemba et al 2013;Nwabanne et al 2013). However, the clay dosage and the temperature respectively have a more significant effect on bleaching capacity since their coefficients are higher, while the negative values of the other coefficients mainly those of quadratic and multiple terms cause a decrease in the bleaching capacity.…”
Section: The Models Coefficients Sign Interpretationsupporting
confidence: 74%
“…Response surface methodology (RSM) is a useful model to study the effect of different factors on the response factor (the intended factor) by simultaneously changing them and performing a limited number of experiments (Ajemba et al, 2013). RSM, which is based on polynomial analysis, is a set of mathematical and statistical techniques used to model and analyze issues when the subject under study is affected by several factors.…”
Section: Introductionmentioning
confidence: 99%
“…6. It was observed that the absorbance and bleaching efficiency generally increased with increase in ANC dosage [24][25][26]4]. This was due to the increase in the surface area of the adsorbent leading to the increase in the pore spaces of the active adsorption site [25].…”
Section: Effect Of Dosage and Contact Time On The Bleaching Efficiencymentioning
confidence: 99%
“…This was due to the increase in the surface area of the adsorbent leading to the increase in the pore spaces of the active adsorption site [25]. However, at 4 g the bleaching efficiency remained constant and dropped as the contact time increased and could have been due to the complete adsorption of the color pigments (beta carotene) onto the available active sites of the adsorbent [26]. A maximum dosage of 4.0 g was observed for acid-activated Nibo with percentage color reduction of 86.0% at 40 min.…”
Section: Effect Of Dosage and Contact Time On The Bleaching Efficiencymentioning
confidence: 99%